Estimated Equations for Water Flow Through Packed Bed of Mono Size Spherical Packing System - nan, nan (Iraqi Journal of Civil Engineering, 2010)
AbstractSemi-empirical equation for water flow through packed bed of sphere particles of mono size packing system has been estimated depending on Buckingham  theorem. Different parameters affecting the pressure drop of fluid flow through packed bed have been studied. These parameters are fluid velocity, bed porosity, bed diameter, sphericity, particle diameter, packing height and wall effect. Several types and kinds of packing materials have been used in this study such as (Pea Gravel, Marbles, Glass Marbles, Black Marbles, Clear Marbles, Acrylic balls and Glass spheres). The diameters of the packing materials used in this model are from the range of (0.2-8.89) cm, the porosity is from the range of (0.3-0.47), the bed diameters is from the range of (7.62 - 15.24) cm and the height of packing is from the range of (26.03 - 55.88) cm. πThe results of all calculations for the estimated equations have been compared with many documented experimental literatures. This comparison gave a very good agreement, and has been represented in curves. The results from Ergun equation using similar conditions have been represented in the curves for the sake of comparison.